Carolina Maria de Jesus e a autorrepresentação literária da exclusão social na América Latina: olhares reversos aos de Eduardo Galeano e Octavio Paz - Larissa Paula Tirloni; Marcelo Marinho (Estudos de Literatura Brasileira Contemporânea)
The Comparative Literature is aimed at approaching cultural identity matters as well as interethnic or intersocial literary representations. Through its wide range of possible literary and cultural readings, the Comparative Literature becomes a useful tool to an alyze transcultural dialogues as a locus of refusals or acceptations for human and social differences. Henceforth, this paper results of a comparative reading focused on Carolina Maria de Jesus autobiographical narrative and its implicit social exclusion l iterary images. In order to achieve that critical goal, this crisscrossed - reading takes into consideration the poetic and social ideas of Mexican diplomat Octavio Paz and Uruguayan journalist Eduardo Galeano. The selected text corpus brings forth literary representations and symbolic images of the society segment that lives in an extreme marginal position, making themselves invisible to other social groups. These out - of - sight people are called “ninguneados” by Octavio Paz, while Galeano pays a tribute to th em in a denouncing poem that presents, from an external point of view, some aspects of their silenced life. Those people are the very human beings whose existence is voluntarily erased or ignored within every cultural manifestations or social relationships that configure hierarchical daily life as well as empirical ways of social living. From an internal point of view, Carolina de Jesus brings into light the silenced life and history of those people condemned to live as outsiders in modern social structures , despite their full belonging to their own people history as well as to the whole humankind history.